MORPHOSTRUCTURAL TRAITS IN INDONESIAN FEMALE GOAT BREEDS OF BOER, BOERKA, KACANG AND ETTAWA CROSS - S. Elieser,; Hartati,; W. P. Putra,; E. Handiwirawan,; R.Hutasoit,; T. L. Tyasi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Morphostructural characterization can be used to identify unique characteristics in different animal breeds and an essential tool for the identification and classification of these breeds.  The objective of this study was to characterize four Indonesian goat breeds based on their morphostructural traits.  A total of 315 female goats (does) at 2.5 - 3.5 years of age were used currently and consisted of 28 Boer, 118 Boerka, 141 Kacang and 28 Ettawa cross. Total eleven body measurements and ten body conformations were measured to describe the morphostructure of goats. Two statistical methods of canonical discriminant analysis (CDA) and hierarchical cluster analysis (HCA) were used to differentiate goat breeds. Body measurement and body index were able to discriminate goat breeds with canonical correlation (Function 1) of 0.81 and 0.77, respectively. According to HCA of morphostructural traits, Boerka and Kacang does are classified into similar cluster.  Body measurement is better for discriminating goat breeds rather than body conformation.